Dental management of hemophiliac child under general anesthesia - R Rayen; V S Hariharan; N Elavazhagan; N Kamalendran; R Varadarajan (Wolters Kluwer Medknow Publications, 2011)
Hemophilia is the most common inherited bleeding disorder. Hemophilic patients should be cosidered as special patients. There is no contraindication to general dental treatment for hemophiliacs, as they generally do not involve bleeding. But caution must be used with any surgical procedures that involve the local and general anesthesia. Such patients should always be managed in the setting of specialized units with appropriate clinical expertise and laboratory support. Recent advances in the management of hemophilia have enabled many hemophiliac patients to receive surgical dental procedures in an outpatient dental care on a routine basis. The purpose of this case report is to provide a few management strategies when providing full mouth rehabilitation under anesthesia and replacement therapies that are available. In addition, overviews of possible complication that may be encountered when providing such treatment are discussed here.